2009
DOI: 10.1261/rna.1472009
|View full text |Cite
|
Sign up to set email alerts
|

A conserved motif of vertebrate Y RNAs essential for chromosomal DNA replication

Abstract: Noncoding Y RNAs are required for the reconstitution of chromosomal DNA replication in late G1 phase template nuclei in a human cell-free system. Y RNA genes are present in all vertebrates and in some isolated nonvertebrates, but the conservation of Y RNA function and key determinants for its function are unknown. Here, we identify a determinant of Y RNA function in DNA replication, which is conserved throughout vertebrate evolution. Vertebrate Y RNAs are able to reconstitute chromosomal DNA replication in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
133
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(141 citation statements)
references
References 47 publications
8
133
0
Order By: Relevance
“…The 83-nt primary hY5 transcript, which is reported to form a very stable hairpin structure (van Gelder et al 1994;Maraia et al 1996) and thus likely renders the 23-and 31-nt regions inaccessible, also triggers substantially lower cell deaths. Interestingly, Gardiner et al (2009) and Wang et al (2014) reported a double-stranded version of the critical 8 nt found in the RNY5 sRNA (5 ′ GUAGUGGG3 ′ ) to be sufficient for RNY1 to support the initiation of DNA replication. However, in our studies it is clear that the hY5 31-and 23-nt processed products triggered cell death is attenuated in the presence of their complementary strands.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The 83-nt primary hY5 transcript, which is reported to form a very stable hairpin structure (van Gelder et al 1994;Maraia et al 1996) and thus likely renders the 23-and 31-nt regions inaccessible, also triggers substantially lower cell deaths. Interestingly, Gardiner et al (2009) and Wang et al (2014) reported a double-stranded version of the critical 8 nt found in the RNY5 sRNA (5 ′ GUAGUGGG3 ′ ) to be sufficient for RNY1 to support the initiation of DNA replication. However, in our studies it is clear that the hY5 31-and 23-nt processed products triggered cell death is attenuated in the presence of their complementary strands.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our studies it is clear that the hY5 31-and 23-nt processed products triggered cell death is attenuated in the presence of their complementary strands. Although Gardiner et al (2009) did not report if a single-stranded version of this sequence was capable of supporting the initiation of replication, one possibility is that the single-stranded 31-and 23-nt sRNAs cause inappropriate and perhaps uncontrolled DNA replication signals in primary cells, triggering cell death. Such processed RNY5-stimulated signals might be less effective in cancer cell lines given their characteristic loss of DNA replication controls inherent with transformed cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In extracts from human somatic cells, reconstitution of chromosomal DNA replication in isolated cell nuclei requires a class of non-coding RNAs termed Y RNAs (Christov et al, 2006;Gardiner et al, 2009;Krude et al, 2009). These are small, structured stem-loop RNAs of between 69-112 nucleotides in length, which are conserved in vertebrate evolution Farris et al, 1995;Mosig et al, 2007;Perreault et al, 2007).…”
Section: Introductionmentioning
confidence: 99%